Respostas
respondido por:
0
Vamos lá
Respondendo
3 - 6a = 0
-6a = -3
Como nenhuma icognita pode ser negativa utilizamos o termo *(-1)
-6a = - 3 *(-1)
6a = 3
a=3/6
ou a=0,5
Espero ter ajudado!!
Bons estudos!!
Respondendo
3 - 6a = 0
-6a = -3
Como nenhuma icognita pode ser negativa utilizamos o termo *(-1)
-6a = - 3 *(-1)
6a = 3
a=3/6
ou a=0,5
Espero ter ajudado!!
Bons estudos!!
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás